QADCGPIC–M: A point kernel shielding code with features for handling bulk shields up to 100 mean free path and stratified shielding configurations. (November 2022) - Basu, Pew; Sarangapani, R.; Venkatraman, B.
Graphical abstract: Highlights: Provision to handle thick shields up to 100 mean free path. Incorporation of modified Kalos' formula for double layer gamma ray exposure buildup factor. Validation of the code in handling bulk and stratified shielding configurations. Abstract: Salient modifications and validations performed on a Point Kernel method based code QADCGPIC, which are important for optimizing shield design is presented in the paper. The geometric progression method based build–up factors (BUFs) for penetration depths of medium up to 100 mean free path is incorporated into the modified QADCGPIC–M code. Further improvement to the code is made by incorporating the modified Kalos' formula of double layer gamma ray exposure build–up factor (DBUF) for the shielding materials used in the design of nuclear and radiological facilities. The modified code is validated by estimating the BUFs, DBUFs, and gamma dose rates at the exit of the shield with Monte Carlo simulation for various shielding configurations of lead, tungsten, iron, and concrete and published values. The validation exercise indicates a good agreement between the computed values by different methods. The incorporation of geometric progression fitting formula and modified Kalos' formula into the QADCGPIC–M code increases the ability of the code to handle bulk shielding and optimization of thicknesses of double layered shielding configurations.